Discrimination against people with mental health problems in the workplace : a comparative analysis - Lake, Rosalind (Rhodes University, Faculty of Law, Law, 2006)
For a long time the rights of disabled persons have been ignored worldwide. A major obstacle faced by disabled persons is discrimination in the workplace. Due to the development of a social approach to disability and the efforts of the Disability Rights Movement, legislation has been passed throughout the world to improve this dire situation. The thesis considers the efficacy of some of these statutes. It is concluded that stigma and negative stereotypes remain a constant hurdle in overcoming discrimination. The forthcoming UN Disability Convention is demonstrative of the recognition of the importance of the needs and rights of disabled people. The convention proposes some innovative measures to overcome stigma and stereotyping. Mental health problems constitute one of the leading causes of disability. The thesis explores how people with mental health problems fit within the concept of people with disabilities and whether they are included in anti-discrimination legislation and affirmative action measures. Special attention is given to statutory definitions of disability, the different forms of discrimination and the concept of reasonable accommodation. A comparative approach is taken to analyse how South Africa's disability law measures up against that of Britain and Australia in terms of its substantive provisions and enforcement thereof. In considering the South African position American and Canadian jurisprudence is consulted in order to aid in interpretation. It is concluded that although South Africa has a comparatively good legislative framework, it is held back by an overly restrictive and medically focused definition of disability. As a result many individuals with mental health difficulties, desirous of obtaining and retaining employment may be excluded from protection against discrimination in the workplace. It is argued that it will be necessary either to amend the Employment Equity Act or for the courts to adhere strictly to the concept of substantive equality in order to ensure that the rights and dignity of people with mental health difficulties are adequately protected.
Keywords: Employees -- Mental health; People with disabilities -- Employment -- South Africa; People with disabilities -- Employment -- Great Britain; People with disabilities -- Employment -- Australia; Discrimination in employment -- Law and legislation -- South Africa; Discrimination in employment -- Law and legislation -- Australia; Discrimination in employment -- Law and legislation -- Great Britain; People with disabilities -- Legal status, laws, etc -- South Africa; People with disabilities -- Legal status, laws, etc. -- Australia; People with disabilities -- Legal status, laws, etc. -- Great Britain